2000
DOI: 10.1021/ma000048x
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Association of Acid-Terminated Poly(dimethylsiloxane)s. 2. Molecular Weight Distributions

Abstract: Association through hydrogen bonding of benzoic acid-terminated poly(dimethylsiloxane) 1 in low-polarity solvents has been studied by FTIR spectroscopy and viscosimetry. At high concentrations, chain extension leads to high viscosity values, whereas at low concentrations, intramolecular hydrogen bonding is responsible for the formation of low-viscosity cyclic species. A quantitative model based on Jacobson-Stockmayer theory and describing the competition between chain extension and macrocyclization is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…The monocarbonyl acide terminated polydimethylsiloxane and the 3,6,9,12-tetraoxotridecanoic acid were synthesized as described in the literature. 3,4 Other reagents were commercially available and used without any further purification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The monocarbonyl acide terminated polydimethylsiloxane and the 3,6,9,12-tetraoxotridecanoic acid were synthesized as described in the literature. 3,4 Other reagents were commercially available and used without any further purification.…”
Section: Methodsmentioning
confidence: 99%
“…The monocarbonyl acide terminated polydimethylsiloxane and the 3,6,9,12-tetraoxotridecanoic acid were synthesized as described in the literature. 3,4 Other reagents were commercially available and used without any further purification.Typical procedure for the synthesis of unimolecular micelles with a hydrophobic shell: PEI-NHCOCH 2 CH 2 C 8 F 17 , 1. The 2H,2H,3H,3H-perfluoroundecaonoic acid (1.06g, 2.16mmol) dissolved in THF (10mL) is added slowly to a solution of carbonyldiimidazol (338mg, 2.09mmol) in THF (10mL).…”
mentioning
confidence: 99%
“…[19,20] Similar behavior -a limited DP in isotropic solution, but polymer-like properties in the mesophase -is observed for systems based on the hydrogen bonds in the carboxylate/ pyridinium ion pair as studied by Griffin and coworkers, [21] while supramolecular arrays of molecules held together by dimerization of carboxylic acid groups have very high DPs in the crystalline state, [22] but low DPs in solution. [23] From these examples it is clear that hydrogen-bonded supramolecular polymers with significant DPs in the isotropic state can only be achieved when the end groups interact more strongly. The most obvious way to increase the interaction strength between hydrogen bonding groups is to further increase the number of hydrogen bonds.…”
Section: Multiple Hydrogen Bondingmentioning
confidence: 99%
“…In an example of a system with relatively weak interactions between benzoic acid terminated poly(dimethylsiloxane)s 20 as monomers, Abed et al [23] reported high viscosities at high concentrations, and low viscosities at low concentrations, which was ascribed to a transition from chain-extended polymers to cyclic species upon dilution. Because the average size of species in a mixture of cycles is only weakly dependent on concentration, the specific viscosity of a solution of cyclic species is expected to be roughly proportional to the concentration.…”
Section: Cyclizationmentioning
confidence: 99%
“…Discrepancy between the Jacobson-Stockmayer theory and experimental data has been observed in other studies in which short linkers have been used, for example during ring formation in covalent polymers, [36][37][38] cyclization of short DNA fragments 39 and cyclization of synthetic supramolecular polymers. 40 It has been suggested that the origin of this discrepancy is due to the fact that short chains are inherently strained in their cyclic conformation and therefore do not obey Gaussian statistics, an important assumption in the derivation of eqn (4). As a result, the effective molarity of the cyclic AB2 monomer is close to, or lower than the effective molarity of the cyclic dimer and the mole fraction of cyclic dimer can surpass the mole fraction of cyclic monomer 33 as is also observed experimentally.…”
Section: This Journal Is ª the Royal Society Of Chemistry 2010mentioning
confidence: 99%